2008
DOI: 10.1161/circulationaha.107.704569
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Insulin Resistance and Cardiovascular Risk During Adolescence

Abstract: Background— Developmental changes in insulin resistance and cardiovascular risk were studied in youths 11 to 19 years of age. Methods and Results— A cohort was randomly selected after blood pressure screening of Minneapolis, Minn, school children. Studies were done 3 times on this cohort and once on their siblings (996 observations on 507 individuals from 363 families). Insulin sensitivity was determined by eugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
157
4
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(186 citation statements)
references
References 47 publications
20
157
4
4
Order By: Relevance
“…Female sex during adolescence has been shown to exert a positive influence on insulin sensitivity, lipids and blood pressure (Moran et al 2008), which is in line with the notion that premenopausal women have a lower risk of developing the metabolic syndrome compared with age-matched men (Isomaa et al 2001, Legato et al 2006, Regitz-Zagrosek et al 2007. No single risk factor or combination of factors has yet been shown to fully explain this, but the fact that risk protection disappears after menopause strongly suggests that female hormones play a protective role.…”
Section: Introductionsupporting
confidence: 64%
“…Female sex during adolescence has been shown to exert a positive influence on insulin sensitivity, lipids and blood pressure (Moran et al 2008), which is in line with the notion that premenopausal women have a lower risk of developing the metabolic syndrome compared with age-matched men (Isomaa et al 2001, Legato et al 2006, Regitz-Zagrosek et al 2007. No single risk factor or combination of factors has yet been shown to fully explain this, but the fact that risk protection disappears after menopause strongly suggests that female hormones play a protective role.…”
Section: Introductionsupporting
confidence: 64%
“…1,2 It is known that similar to older individuals, HT in young age coexists with features of metabolic syndrome, such as overweight/obesity, hyperinsulinaemia/insulin resistance and dyslipidaemia. [3][4][5] It is even suggested that the pathophysiologic precursors of adult HT originate earlier in life.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, an overall worsening of insulin sensitivity, lipid levels and blood pressure in adolescent male subjects may occur despite a minimal alteration in total body fat. 1 No studies have been carried out on these lean individuals on whether the presence of these risk factors, including HT, is owing to the preferential visceral deposition of adipose tissue, as documented by studies in overweight/obese subjects. [8][9][10] Despite fatness being associated with insulin resistance and HT, it is clear that obesity per se cannot fully explain the development of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…increased adiposity was more enhanced in female than male rat offspring (Bayol et al 2001). Boys at 19 years of age have a higher lean body mass than girls at the same age, but they also have higher prevalence of insulin resistance (Moran et al 2006). among children at the age of five, girls have higher insulin resistance human _ ontogenetic s than boys.…”
Section: Introductionmentioning
confidence: 98%